T.H. Gallaudet and Edward Miner Gallaudet papers - Gallaudet, T. H. (Thomas Hopkins), 1787-1851.; Boatner, Maxine Tull.; Gallaudet, Edward Miner, 1837-1917.
T.H. Gallaudet's papers include correspondence, diaries, journal and letterbook, poetry and composition books kept while he attended Yale, account book, genealogical studies, printed matter, memorabilia, and other papers. Subjects include the American Asylum, at Hartford, for the Education and Instruction of the Deaf and Dumb, Hartford, Conn. Edward Miner Gallaudet's papers include correspondence, diaries, journals, speeches, memoir, articles, and other papers. Subjects include the Columbia Institution for the Deaf (Washington, D.C.) and Gallaudet College. Includes Gallaudet family photographs and papers of Maxine Tull Boatner, biographer of Edward Miner Gallaudet. Boatner's papers consist chiefly of correspondence, printed matter, and page proofs of Voice of the Deaf; A Biography of Edward Miner Gallaudet (1959).
Educators.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gallaudet family; American Asylum, at Hartford, for the Education and Instruction of the Deaf and Dumb; Columbia Institution for the Deaf (Washington, D.C.); Gallaudet College; Yale University -- Students; Deaf -- Education; Educators